2010
DOI: 10.1007/s11252-010-0134-7
|View full text |Cite
|
Sign up to set email alerts
|

Learning about restoration of urban ecosystems: a case study integrating public participation, stormwater management, and ecological research

Abstract: Restoration of ecosystem functions in urban environments is made challenging by 1) a public that often lacks understanding of ecological principles, 2) inadequate evidence of the effectiveness of restoration practices, and 3) difficulty integrating social and biophysical factors in studies of urban ecosystems. This paper describes a case study in which potential solutions to these challenges were explored. We facilitated collaborative learning through public participation in the design and implementation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Communities have been focal points since early attempts to address urban issues using nature-based solutions [21,22,24]. Over the past decade there has been a rapid increase in the number of Citizen Science initiatives which offers an attractive solution for on-going monitoring [134][135][136], and the engagement and empowerment of communities to lead urban green actions. A participatory planning process is critical in identifying and mainstreaming nature-based solutions in towns and cities.…”
Section: Discussionmentioning
confidence: 99%
“…Communities have been focal points since early attempts to address urban issues using nature-based solutions [21,22,24]. Over the past decade there has been a rapid increase in the number of Citizen Science initiatives which offers an attractive solution for on-going monitoring [134][135][136], and the engagement and empowerment of communities to lead urban green actions. A participatory planning process is critical in identifying and mainstreaming nature-based solutions in towns and cities.…”
Section: Discussionmentioning
confidence: 99%
“…urban land and impoundments) are linked to the absence of Topeka shiners, conservation and rehabilitation efforts may help minimize the anthropogenic impact on Topeka shiners and other native fishes in these streams. For example, establishing riparian buffers around streams may reduce the impact of urbanization and agricultural practices on these streams (Wang et al 2001;Herringshaw et al 2010). By identifying factors associated with the presence and absence of Topeka shiner populations this study may help managers conserve current Topeka shiner populations and identify sites for future reclamation and conservation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Further motivation for this project comes from the finding that coastal risk management policies should promote private adaptation initiative by integrating it into public adaptation strategies and efforts [27]. In addition to the climate adaptation literature, examples of projects can be found that provide evidence of engaged private citizens active in public stormwater efforts [34][35][36]. Previous studies in the MLSCA identified residents of a Duluth, Minnesota neighborhood that understood the connection between excess stormwater and Lake Superior water quality [37].…”
Section: Private Citizen Participationmentioning
confidence: 99%